2020
DOI: 10.1007/s13312-021-2125-6
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Viral Clearance in Children With SARS-CoV-2 Infection in Rajasthan, India

Abstract: Objective To study the clinical and laboratory profile and to assess period for viral clearance in COVID 19 children. Methods We reviewed hospital records of children (<18 years) admitted from 1 April to 31 May, 2020 at a tertiary-care public hospital and identified those positive for severe acute respiratory syndrome corona virus (SARS-CoV-2) by RT-PCR of respiratory secretions. Results 81.2% of the 85 children studied were asymptomatic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In addition, there is growing evidence that the prolonged presence of viral RNA does not necessarily imply infectivity. A recent study conducted in children with COVID-19 showed an average viral spread duration of about 11 and 23 days from the onset of symptoms through the respiratory tract and gastrointestinal tract, respectively [44]. A study on virus culture and contact traceability suggested that patients with mild to moderate COVID-19 are highly unlikely to be infectious beyond 10 days after the onset of symptoms [45].…”
Section: After How Many Days Should the Swab Be Repeated In Case Of Positive Sars-cov-2 Result?mentioning
confidence: 99%
“…In addition, there is growing evidence that the prolonged presence of viral RNA does not necessarily imply infectivity. A recent study conducted in children with COVID-19 showed an average viral spread duration of about 11 and 23 days from the onset of symptoms through the respiratory tract and gastrointestinal tract, respectively [44]. A study on virus culture and contact traceability suggested that patients with mild to moderate COVID-19 are highly unlikely to be infectious beyond 10 days after the onset of symptoms [45].…”
Section: After How Many Days Should the Swab Be Repeated In Case Of Positive Sars-cov-2 Result?mentioning
confidence: 99%
“…The negative RT-PCR in the nasopharyngeal swab could be attributed to delay in testing after symptom appearance, low viral load in the sample, or viral clearance as she had completed 14 days from the symptom onset and it is known that the median duration for 50% viral clearance is around 7 days, and almost all children get a viral clearance within 14 days. 24 The extensive negative evaluation for stroke in this child had financial implications for the family. Early testing for SARS-CoV-2 by RT-PCR and serology would have helped in arriving at an early diagnosis especially amid the pandemic where COVID-19 infection-associated stroke might be more common than other rare causes of childhood stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The negative RT-PCR in the nasopharyngeal swab could be attributed to delay in testing after symptom appearance, low viral load in the sample, or viral clearance as she had completed 14 days from the symptom onset and it is known that the median duration for 50% viral clearance is around 7 days, and almost all children get a viral clearance within 14 days. 24…”
Section: Discussionmentioning
confidence: 99%
“…Regarding VC we found three relevant studies: Gupta et al ( 22 ) analysed data of 85 children and adolescents (aged 0–18) who were tested positive for SARS-CoV-2 and admitted to hospital during April and May 2020 in Rajasthan/India. The participants were tested by PCR every 3 days.…”
Section: Discussionmentioning
confidence: 99%